Comparison of the effects of insulin and SGLT2 inhibitor on the Renal Renin-Angiotensin system in type 1 diabetes mice. (April 2020) - Miyata, Kana N.; Zhao, Shuiling; Wu, Chin-Han; Lo, Chao-Sheng; Ghosh, Anindya; Chenier, Isabelle; Filep, Janos G.; Ingelfinger, Julie R.; Zhang, Shao-Ling; Chan, John S.D.
Highlights: Intrarenal angiotensinogen expression is reduced by insulin in type 1 diabetes model. Intrarenal angiotensinogen expression is unchanged by SGLT2 inhibitor. Insulin, but not SGLT2 inhibitor, attenuates systemic hypertension. The effect on albuminuria reduction is more pronounced with insulin than SGLT2 inhibitor. Abstract: Aims: SGLT2 inhibitors have been proposed as an adjunct to insulin therapy for glycemic control in type 1 diabetes (T1D) patients. However, concern has been raised due to an increase in renin–angiotensin-system (RAS) activity reported in a clinical trial in which an SGLT2 inhibitor was added while insulin dose was reduced in T1D patients. We previously reported that insulin inhibits intrarenal angiotensinogen ( Agt ) gene transcription and RAS activation. We hypothesized that insulin, rather than SGLT2 inhibition might regulate the intrarenal RAS. Methods: We compared RAS activity in non-diabetic wild type mice, Akita mice (T1D model) and Akita mice treated with insulin or the SGLT2 inhibitor canagliflozin. Results: Treatment of Akita mice with insulin or canagliflozin produced similar reductions in blood glucose, whereas insulin, but not canagliflozin, reduced elevated systolic blood pressure. Akita mice exhibited increased renal Agt mRNA/protein expression, which was attenuated by insulin, but not by canagliflozin. Furthermore, insulin was more effective than canagliflozin in lowering kidney weight and albuminuria. Conclusions: Insulin, but not canagliflozin, lowers intrarenal RAS activity in Akita mice. Our findings can be of potential clinical importance, especially for T1D patients who are not on RAS inhibitors at the time of adding SGLT2 inhibitors.